Hepatectomy for liver metastases from gastric cancer: a systematic review. Issue 1 (December 2017) - Liao, Ying-Yang; Peng, Ning-Fu; Long, Di; Yu, Peng-Cheng; Zhang, Sen; Zhong, Jian-Hong; Li, Le-Qun
Abstract Background Official guidelines recommend palliative treatments for patients with liver metastases from gastric cancer. However, many case series reported that hepatectomy for such cases is safe and effective. This systematic review compares the overall survival between hepatectomy and palliative therapy in patients with liver metastases from gastric cancer. Methods Two independent reviewers performed a systematic search of literature in EMBASE and PubMed, updated until 26 October 2016. The Newcastle-Ottawa score for cohort studies was used for quality assessment of included studies. Results A total of eight cohort studies involving 196 patients in the hepatectomy arm and 481 in the palliative arm were included. Median overall survival of patients in the two arms was 23.7 (range, 13.0 to 48.0) and 7.6 (range, 5.5 to 15.2), respectively. Median rates of overall survival of the two arms were 69, 40, 33 and 27, 8, 4% at 1, 2, and 3 years, respectively. Comparing with palliative therapy, hepatectomy was associated with significantly lower mortality at 1 year (odds ratio 0.17, P < 0.001) and 2 years (odds ratio 0.15, P < 0.001). Among the patients who underwent hepatectomy, Asian cohorts showed higher median rates of overall survival than Western cohorts at 1 year (76 vs. 60%), 2 years (47 vs. 30%) and 3 years (39 vs. 23%). Conclusions Hepatectomy in the management of liver metastases from gastric cancer can be considered effective. In the elective setting, hepatectomy provides a potential alternative to palliative therapy.